Bilateral Approach to Ecosystem-Based Marine Management in the Barents Sea - Rodríguez, Nicolás J. I. (Journal of Northern Studies, 2011)
In 2006 the Government of Norway presented a marine management plan for the Norwegian part of the Barents Sea, and a Northern strategy was introduced as a supportive regional instrument. For the first time the method of ecosystem approach is applied in a Norwegian context as a principle in the Barents Sea plan. The main elements of the plan consist of ecosystem indicators, management goals and planning maps indicating biologically vulnerable areas where petroleum activity cannot be performed. An important question is the relation between the plan and existing management regimes in laws and through bilateral cooperation in the Barents Sea, in respect of both biological resources and non-renewable resource extraction. A general, political plan such as the Barents Sea plan must have some sort of consistency among already existing legal regimes, sector management and bilateral cooperation in order to succeed. If underlying regimes are not sustainable in their practice, neither can a general plan be. The article examines the basis for an implementation of an ecosystem approach comparing the bilateral management of Norway and Russia in the Barents Sea using the question of fishery resources in the region as a case.